Nonlinear Characteristic of Spherical Joints with Clearance - Jing,Zhang (2015)
ABSTRACT: Joints in deployable structures can degrade the stiffness and the stability of spacecraft. In this study, the nonlinear stiffness of spherical joints is investigated. The traditional contact model of spherical joints based on non-conforming contact assumption is presented. A new contact model for spherical joints based on the Winkler model and geometric constraints is established to calculate the stiffness of spherical joints with small clearances. The finite element model (FEM) of spherical joints is built to evaluate the accuracy of the theoretical model. The effects of the clearance and the contact force of spherical joints on the deformation of joints are investigated. When compared with FEM results, the error of the new spherical model is smaller than that of the traditional contact model when the clearance of spherical joint is not excessively large. The new contact model for spherical joint is more accurate than the traditional contact model when the clearance of spherical joint is large.